Comparative Approaches to Antimicrobial Resistance Testing in Sepsis: E-Test and Molecular Diagnostics – A Scoping Review - Putu Ngurah Pradnya Wibawa; Ni Putu Lia Juliantini; Ni Luh Putu Serly Ekayanti (CV. Publikasi Indonesia, 2026)
Sepsis remains a major global health problem with high morbidity and mortality. Rapid antimicrobial susceptibility testing (AST) is essential, but conventional methods are time-consuming and may delay appropriate therapy. This study aimed to compare phenotypic methods, particularly the E-test, and molecular diagnostics for antimicrobial susceptibility testing in sepsis. A scoping review was conducted using PubMed, ScienceDirect, and other sources for studies published between 2016 and 2026. From 214 identified records, 10 studies met the inclusion criteria and were analyzed. Molecular diagnostics provided results within 1–8 hours, while rapid phenotypic methods required 3–7 hours, compared to 48–96 hours for conventional methods. Molecular approaches showed high resistance detection accuracy (up to 99%), whereas phenotypic methods demonstrated high agreement with reference standards (>95–99%). Rapid diagnostics improved antimicrobial therapy optimization, with treatment modification reported in up to 21% of patients. Phenotypic and molecular methods have complementary strengths. Molecular diagnostics offer speed, while phenotypic methods such as the E-test ensure accuracy. An integrated approach may improve antimicrobial stewardship and clinical outcomes in sepsis.